Improved husbandry measures to enhance reproducibility of wound healing studies in the Leprdb/db mouse - May Barakat; Brian P. David; Junhe Shi; Angela Xu; Terry W. Moore; Lin Chen; Luisa A. DiPietro (Animal Models and Experimental Medicine, 2025)
Abstract The Leprdb/db mouse is a common and well‐studied model of type II diabetes mellitus that is often employed in biomedical research. Despite being one of the most commonly used models for the investigation of diabetic wound healing, there are a few specific guidelines for its husbandry, and wound complications such as infection and expansion are common. This study presents a modified animal husbandry approach for the Leprdb/db mouse to reduce the incidence of complications during wound healing experiments. Compared to standard rodent housing protocols, the use of this modified protocol leads to decreased rates of complications among experimental animals across several experiments. The protocol includes increased cage size, decreased housing density, and more frequent cage replacements. The use of improved husbandry for the Leprdb/db mouse decreases the total number of animals required, minimizes harm during experimentation, and improves the consistency and reproducibility of wound healing studies.